Pediatric Hallux Valgus - S. Liu, David; P. Miller, Christopher; Cepollina Raduan, Fernando (Journal of the Foot & Ankle, 2024)
Pediatric hallux valgus is a common condition that may present with various symptoms. In children with underlying neuromuscular diagnoses, treatment strategies can be fairly straightforward: if the deformity is painful and challenging to manage due to hygienic or shoewear problems, first metatarsophalangeal joint arthrodesis is indicated as a safe, reliable, and single surgical procedure. In ambulatory healthy children, skeletal maturity status and the amount of growth remaining should be strongly considered. Surgical treatment options are indicated for patients with recalcitrant pain and symptoms despite a dedicated effort towards activity and shoewear modifications. If possible, surgery should be delayed until complete closure of the physes. Various procedures exist for the correction of hallux valgus, and surgeons should critically analyze and select the most appropriate option. Recurrence may be a significant risk, particularly in the pediatric and adolescent population.